Comparing constitutional protection of human rights in Europe - Novak, Aleš (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The article aims to demonstrate the usefulness of comparative method in the field of constitutional law, in particular in the field of human rights provisions at the constitutional level. It tries to disprove the common assumption that the human rights provisions in different constitutions are almost identical and that the legal unification is in that respect almost complete. The analysis of the European constitutions unveils a somewhat different picture. In part, that assumption is correct. The vast majority of the constitutions incorporate what the authors have called a "common core of human rights", some 20 provisions that can be found in almost all European constitutions (e.g. right to freedom, principle of equality, freedom of expression, freedom of assembly, freedom of association etc.). Equally important are, however, certain clusters of human rights provisions (or absence thereof) that are typical of certain groups of constitutions, but not of others. The authors have called these particular clusters of provisions or certain combinations of provision a constitutional profile. Based on the detailed analysis of the constitutions, four distinct constitutional profiles could arguably be recognised, which the authors have described as Nordic, Romanic, Germanic and Common Law group.
Keywords: Europe; Evropa; ustave; primerjalno pravo; ustavno pravo; človekove pravice; human rights; pravno varstvo